A experiência da misericórdia em Teresa de Jesus uma leitura teológica do livro da vida (1-9) - Machado, Everton Ricardo Berny (2023)
This dissertation thesis proposes to study the experience of divine mercy performed by Saint Teresa of Jesus and narrated in the first nine chapters of the Book of Her Life. Starting from a contextualization of the author, going through an analysis of the indicated text, the study leads to a Narrative Theology approach, which suggests overcoming the distance between Dogmatic and Mystical. Via biographical research based on Teresian specialist writers, the study focuses on the theme of mercy. This topic has gained relevance in recent years due to Pope Francis’s Magisterium. The present investigation wants to contribute to this discussion as it highlights the importance of this subject in the life of the Carmelite mystic and Doctor of the Church, Teresa of Ávila. The divine mercy experience is the base of her mystical life. Likewise, it is at the center of Christian life and guides to ecclesial and missionary dynamism. The study of such an experience enables the reader to interpret his own experience. Therefore, the analysis focuses on the experiential attribute of the Christian faith intertwined with theological formulations. Teresa will make a theological reading of her life and list elements for each reader to do the same.